ΑΔΕΛΦΟΤΗΤΑ, ΚΟΜΠΑΝΙΑ, ΚΟΙΝΟΤΗΤΑ. ΓΙΑ ΜΙΑ ΤΥΠΟΛΟΓΙΑ ΤΩΝ ΕΛΛΗΝΙΚΩΝ ΚΟΙΝΟΤΗΤΩΝ ΤΗΣ ΚΕΝΤΡΙΚΗΣ ΕΥΡΩΠΗΣ, ΜΕ ΑΦΟΡΜΗ ΤΟ ΑΓΝΩΣΤΟ ΚΑΤΑΣΤΑΤΙΚΟ TOY MISKOLC (1801) - ΚΑΤΣΙΑΡΔΗ-HERING ΟΛΓΑ (Eoa kai Esperia, 2007)
This is one of the articles based on the research carried out in the contextof the European research programme PYTHAGORAS II titled «Greekcommunities and the European world (13th-19th centuries). Aspects of selfadministration,social organization, formation of identities», which was realized in the Department of History and Archaeology at the University ofAthens. In the text are discussed the results of the research made by the collaborators of the programme in the archives of Venice, Vienna, Hungary, Romania and referring to the organization of the Greek communities in thesecities and lands. The gathered material (especially statutes referring to theadministration of the communities, schools etc.), as well as the up to nowknown archival material and literature conducted us to conclusions discussedin this paper. The above article provides an attempt at typology of six groupsof organization, beginning from the case ’confraternity’/community of Venice (15th century onward), to those of the Transylvanian ’companies’ (17th century onward) as well as the Habsburg lands communities (18th - beginning19th centuries). The typology is based on the data-base form systematized material, which gives answers concerning the comparison of the various typesand terms of administration, the relations between the Greek and othersettlers and the reception-countries too, the role of the home tradition andthat of the various group-immigrants from the Balkan lands, the developmentin the organization forms during the time, the influence of the emergence ofnationalism. The article completes the publication and the comparative analysis of theunknown, till now, statutes of the Greek ’company’/community in Miskolc/Hungary (1801) found in the Borsod archive of Miskolc.